2020
DOI: 10.1177/0194599820930214
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngology in the Time of Corona: Assessing Operative Impact and Risk During the COVID‐19 Crisis

Abstract: Objective Limited research exists on the coronavirus disease 2019 (COVID-19) pandemic pertaining to otolaryngology–head and neck surgery (OHNS). The present study seeks to understand the response of OHNS workflows in the context of policy changes and to contribute to developing preparatory guidelines for perioperative management in OHNS. Study Design Retrospective cohort study. Setting Pediatric and general adult academic medical centers and a Comprehensive Cancer Center (CCC). Subjects and Methods OHNS cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
0
15
0
2
Order By: Relevance
“…While this information has yet to be described for cleft surgeries, similar observations were noted in patients undergoing other surgical procedures. 13,25,26 Interestingly, we did not observe a statistically significant differences in time under anesthesia despite the addition of supplementary perioperative protocols. It should be noted, however, that our preoperative screening protocols allowed our institution to implement less disruptive perioperative protocols given its reliability at preventing COVID-positive patients from entering the operating room.…”
Section: Discussionmentioning
confidence: 50%
“…While this information has yet to be described for cleft surgeries, similar observations were noted in patients undergoing other surgical procedures. 13,25,26 Interestingly, we did not observe a statistically significant differences in time under anesthesia despite the addition of supplementary perioperative protocols. It should be noted, however, that our preoperative screening protocols allowed our institution to implement less disruptive perioperative protocols given its reliability at preventing COVID-positive patients from entering the operating room.…”
Section: Discussionmentioning
confidence: 50%
“…Numerous otolaryngological publications discuss the high risk of ENT procedures and emphasize the need for comprehensive guidelines [ 22 24 ]. In practice, Kuhar et al reported an extremely high percentage of aerosol-generating otolaryngological procedures in Ohio [ 25 ]. Furthermore, a few studies documented the development of patient numbers during the COVID-19 pandemic, but mostly lack in-depth statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a few studies documented the development of patient numbers during the COVID-19 pandemic, but mostly lack in-depth statistical analysis. Kuhar et al found a large drop in surgical procedures in the United States, but did not study further subcategories [ 25 ]. Ralli et al demonstrated a decrease in operative procedures mainly driven by a drop in procedures for abscesses and nasal bone fractures in Italy, while numbers of cancer surgery remained stable [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] Amid this intense focus on the tracheotomy procedure, including indications, timing, and technique, far less attention has been afforded to several high-stakes postprocedural considerations. [24][25][26][27][28][29] Many pressing issues came to light only after significant clinical experience of downstream effects of pandemic care-such as occlusion risk due to highly tenacious COVID-19 secretion or bleeding risk from aggressive prophylactic anticoagulation to counteract thrombotic stroke risks in COVID-19. 30,31 Furthermore, many health care workers are still inadequately trained regarding precautions during aerosol-generating procedures (AGPs).…”
mentioning
confidence: 99%